Global Assessment of Emerging Contaminant Removal in Wastewater Treatment Plants: In Silico Hazard Screening and Risk Evaluation - Arianna Sgariboldi; Elena Posté; Nicola Chirico; Alessandro Sangion; Marco Evangelista; Cristiana Morosini; Andrea Re; Vincenzo Torretta; Ester Papa (Toxics)
Pharmaceuticals and personal care products (PPCPs) are emerging contaminants (ECs), whose presence in the environment is of increasing concern due to their widespread use and possible detrimental effects on wildlife and humans. These chemicals may present multiple hazardous properties such as environmental persistence, toxicity, high mobility, and the potential for bioaccumulation. In this study, extended bibliographic research was conducted to characterize the removal efficiency (RE) of PPCPs in wastewater treatment plants (WWTPs) considering different technologies. Measured values of RE were collected from the literature or calculated for 251 compounds. The molecular structure of the 245 PPCPs were used as the input to generate predictions of multiple properties using several QSAR tools, such as the OECD Toolbox, OPERA, EPI Suite™, and QSAR-ME Profiler. These predictions were compared to regulatory thresholds to identify hazardous chemicals and to screen persistent, mobile and toxic (PMT) or persistent, bioaccumulative and toxic (PBT) substances. Finally, chemicals were prioritized by combining values of RE and QSAR predictions for multiple properties. A total of 16 out of the 245 molecules were prioritized as the most hazardous compounds to the aquatic environment and, among these, six were associated with potential risk due to their exposure concentrations reported in the literature.